HUBUNGAN TINGKAT STRES DAN KECEMASAN DENGAN MEKANISME KOPING PADA MAHASISWA KEPERAWATAN UPN VETERAN JAKARTA DI MASA PANDEMI COVID-19 - Hopipah Indah Nursobah, Hopipah I.N (2021)
Clinical practice activities can trigger stress and anxiety in students, especially during the COVID-19 pandemic. One of the efforts that can be made to deal with this problem is to implement a coping mechanism. This study aims to determine the relationship between stress and anxiety levels with coping mechanisms for nursing students at UPN Veteran Jakarta during the COVID-19 pandemic. This type of research is quantitative with a cross sectional design. The sampling technique of the study was random sampling as many as 203 nursing students. The questionnaires used were PSS, ZSAS, and The Brief Cope. The results showed that students experienced moderate stress (68.5%) and mild stress (31.5%), mild anxiety (54.2%) and normal anxiety (45.8%). The results of the bivariate test showed that there was a relationship between stress levels with problem-focused coping mechanisms (p=0.020) and emotional-focused coping mechanisms (p=0.046). The test results also showed that there was a relationship between the level of anxiety with problem-focused coping mechanisms (p=0.002) and emotional-focused coping mechanisms (p=0.016). It is necessary to conduct a self-evaluation of each student regarding the coping mechanisms that have been carried out whether effective or not and the role of nurses as counselors and nursing care providers is needed in dealing with stress and anxiety problems.